Conflict Resolution in The Meaning of Space in Conflicts Over Green Space Production - Rianti Jihan Mawarni Kibas (International Journal Labs, 2026)
Urban green space development in rapidly urbanizing cities often creates conflicts between governments, private actors, and local communities due to differences in interests, spatial values, and power relations. In Indonesia, particularly in DKI Jakarta, green space production is frequently implemented through technocratic and development-oriented approaches that overlook the lived experiences and socio-economic dependence of communities on urban space. Therefore, this study aims to identify the different meanings of space constructed by actors involved in green space conflicts and to analyze the conflict resolution approaches applied in these disputes. This research employed a qualitative descriptive method using secondary data and a literature review. Articles related to green space conflicts in DKI Jakarta published between 2020 and 2025 were collected from Google Scholar and analyzed through coding, categorization, and interpretive analysis. The findings reveal that governments and developers tend to produce space as conceived space, characterized by legalistic, technocratic, and economically oriented perspectives, whereas communities experience space as lived space, connected to social identity, livelihood, and collective memory. Existing conflict resolution efforts remain administrative, reactive, and top-down such as relocation, outreach, and mediation and thus fail to address unequal power relations and conflicting spatial meanings. This study concludes that sustainable conflict resolution in green space production requires participatory planning, values-based dialogue, and transformation of power relations to create socially just and inclusive urban development.